Marketing Efficiency Analysis of Oil Palm (Elaeis guneensis jacq) Self-Help Pattern in Wande Village, Dangia Sub-district, East Kolaka Regency - Nela Ariani; Surni; Fahria Nadiryati Sadimantara (International Journal of Technology and Education Research, 2025)
This study aims to (1) determine the self-help pattern of marketing channels for oil palm in Wande Village Dangia District East Kolaka Regency, (2) find out the size of the marketing of palm oil in Wande Village Dangia District, East Kolaka Regency, (3) find out the structure of the independent smallholder palm oil market, (4) determine the efficiency of the marketing channels for oil palm in Wande Village Dangia District East Kolaka Regency. This research was conducted in Wande Village Dangia District East Kolaka Regency from May to August 2023. This study descriptive analysis, marketing margin analysis and marketing efficiency (farmer's share). The number of respondents to independent oil palm smallholders was 30 people using the simple random sampling technique, and the collecting traders were 1 person using the snowball sampling technique. Based on the results of the study indicate that (1) the marketing channel consists of one channel, namely: (a) Farmers-Intermediary traders-Consumers (2) the marketing margin obtained is Rp200. The results of the analysis regarding the percentage of the share of the price received by the producer (farmer's share) is as much as 89%, this shows that the marketing of palm oil runs efficiently